SUSTAINABILITY AND DEMOCRATIC SCHOOL MANAGEMENT - Baade, Joel Haroldo; dos Santos, Adelcio Machado; Hulse, Levi; Simão, Vera Lúcia; Bonin, Joel Cezar; Silva Ogoshi, Rosana Claudio (International Journal of Research -GRANTHAALAYAH, 2019)
Motivation/Background: Sustainability is established on economic, environmental and social pillars, which are understood as inseparable. This demands changes of paradigms and the construction of new models of living, which are directly connected to education. In this context, assuming that people’s actions are more dependent on consolidated habits than on conscience, this essay hopes to demonstrate that democratic management is an irrevocable imperative towards a sustainable society. Method: Methodologically, the research is of a standard nature, as we used qualitative, descriptive and exploratory approaches. As for the procedures, it can be classified as a bibliographic and documental research study. Results and Conclusions: It was concluded that democratic management in education is of great importance for the consolidation of the paradigm of sustainability since schools have a key role in the formation of citizens.